2020
DOI: 10.1088/1755-1315/498/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Study of sediment deposition at Tanjung Laboh due to jetty structural

Abstract: Changes in coastal areas are due to factors such as natural factors. In recent years human activities and coastal development have contributed greatly to the change of the coast. Concerned with this problem, a study was conducted on the coast of Tanjung Laboh in March 2019 to collect oceanographic data related to coastal change. The purpose of this study was to compare the distribution of sediment size in jetty structure areas and unstructured areas. Specific gravity has been compared between sampling lines A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previous studies have reported significant beach accretion on the updrift side in response to jetty constructions (Hapke et al, 2013;Garel et al, 2015;Wang et al, 2022). Salleh and Nadzir (2020) showed that flow velocity and current direction around a jetty significantly affected the deposition of coastal sediments. In the United States, Hein et al (2019) presented that the northwards diffracted/refracted waves induced sediment accretion proximal to the south of the jetty and delivered the sediment across the jetty to an adjacent area.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have reported significant beach accretion on the updrift side in response to jetty constructions (Hapke et al, 2013;Garel et al, 2015;Wang et al, 2022). Salleh and Nadzir (2020) showed that flow velocity and current direction around a jetty significantly affected the deposition of coastal sediments. In the United States, Hein et al (2019) presented that the northwards diffracted/refracted waves induced sediment accretion proximal to the south of the jetty and delivered the sediment across the jetty to an adjacent area.…”
Section: Introductionmentioning
confidence: 94%